Analisis Laporan Arus Kas untuk Menilai Kinerja Keuangan PT. Pertamina (Persero),Tbk Periode 2016-2020 - Ananda Syahrina; Hendra Harmain; Nur Ahmadi Bi Rahmani (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstrakCash is a medium of exchange owned by the company to be ready to be used in company transaction at any time desired. In the statement of financial position,cash is the most current and most frequently changing asset. The purpose of this study is to assess the companyâ€™s financial performance through cash flow statements. Thus research is a qualitative data in the form of financial statement and company cash flow reports for the period 2016-2020. The result of study show that the value of 3 ratios is good and 2 ratios are not good, so the overall financial performance of PT Pertamina is considered quite good, Seen from the cash flow pattern with value of cash flow from operating activities (+) cash flow from investing activities (-) and also cash flow financing activities (-) means that the company uses its excess operating cash flow to buy fixed assets, make investments and pay long-term debts to creditors or maake private payments and cash dividends to owners or inventors.Â Keywords : Ratio of Cash Flow, Financial Statement, Financial Performance